THE EFFECT OF GOVERNMENT SPENDING, DOMESTIC INVESTMENT AND FOREIGN DEBT ON GROSS DOMESTIC PRODUCT IN INDONESIA - Fanny Nailufar; Ichwanul Ichsan; Cut Putri Mellita Sari; Hijri Juliansyah (LPPM Universitas Malikussaleh, 2023)
This study aims to analyze the effect of government spending, domestic investment and foreign debt on gross domestic product in Indonesia. The independent variables in this study are Government Expenditure, Domestic Investment and Foreign Debt while the dependent variable is Gross Domestic Product. The data used in this research is secondary data for the period 1998-2021. The analytical model used in this study is the multiple linear regression model with the Ordinary Least Square (OLS) method. Based on the results of the study, it shows that government spending and foreign debt have a significant and significant effect on gross domestic product in Indonesia while domestic investment has no effect and is not significant on gross domestic product in Indonesia while simultaneously government spending, domestic investment and foreign debt jointly affect the gross domestic product in Indonesia. The test results for the coefficient of determination show that there is a relationship between the independent variables and the dependent variable in this study of 98.57%, which means that the other 01.42% is influenced by other variables outside of this study.